Association of plasma neutrophil gelatinase-associated lipocalin (NGAL) with sepsis and acute kidney dysfunction. (June 2013) - Mårtensson, Johan; Bell, Max; Xu, Shengyuan; Bottai, Matteo; Ravn, Bo; Venge, Per; Martling, Claes-Roland
Abstract Objective: Neutrophil gelatinase-associated lipocalin (NGAL) is secreted by injured kidney cells as well as by activated neutrophils in response to bacterial infections. We assessed the influence of acute renal dysfunction on the association between plasma NGAL and sepsis. Methods: NGAL was measured daily in 138 critically ill patients. Simultaneous recordings of sepsis status and fluctuations in renal function were made. Results: Elevated NGAL was associated with sepsis independent of level of acute renal dysfunction. A cut-off value of 98 ng/mL distinguished sepsis from systemic inflammation with high sensitivity (0.77) and specificity (0.79). Conclusions: Plasma NGAL can help clinicians to identify bacterial infections in critically ill patients.